Dippy Cuppy Cake Company / Haliza Hacho ... [et al.] - Hacho, Haliza; Abdul Hafid, Hasmi; Patrick, Maily; Mahmud, Muliaty; Fridrict, Ninalyn (2010)
Bakery industry nowadays is booming and getting attention by many people. Entrepreneurs are trying to use their creativity and skills in order to capture a high customer's satisfaction through attractive decorations and its nutrition. As we know, people are concern with their health and thus, there are many businesses that produce and sell cupcakes containing low sugar and low fat. They take the customer satisfaction as their main priority. In western country, there are many shops that are specializing in producing as well as selling cupcakes as their business. However, in our country itself, the cupcake business is relatively new and still growing. This business has its own potential to grow in the future. So, we grab this opportunity to undergo a cupcake business and operate a business called Dippy Cuppy Cake Company in order to gain profit as well as to achieve customers' satisfaction. Our project is about cupcake business which is to produce and sell cupcakes. We will offer a variety of high quality of cupcakes and all cupcakes will be made by us in our kitchen. Our prospect is that this business will be developed and expanded in the future as people nowadays are more prefer to have cupcakes in their occasion and also as desserts. Dippy Cuppy Cake Company has come into existence from a unique venture consisted of young energetic Malaysian personnel believing we have the synergy towards achieving our vision, which is within the next five years, Dippy Cuppy Cake Company will be a well-establish bakery shop (specialized in Cupcake) in the Sabah area by consistently providing the combination of perfectly prepared cupcakes and outstanding service that creates an extraordinary dessert experience, with a continued commitment to incorporating wholesome, natural ingredients and promoting business practices that respect the earth and the environment. Our target market is consists of the people in Kota Kinabalu area. Cupcake is for everyone, and thus we evaluate that every person are afford and willing to buy our cupcakes. Individuals who purchase our cupcakes will be people who are in middle to upper class. Corporate people are also one of our target markets as they tend to have celebrations and event.